Growth performance of cabbage (Brassica oleraceae var capitata cv Delta Green and Ky Cross) under netted rain shelter using fertigation system - Mahirah, Mat Yasim (2015)
A field experiment on the effect of fertigation system to the production of cabbage (Brassica oleraceae var capitata cv Delta Green and KY Cross) grown using fertigation system under netted rain shelter was carried out. This experiment is conducted at the Agropark, Universiti Malaysia Kelantan, Jeli campus. The growth parameter of both cabbage cultivars were taken. The plant height, number of leaves, diameter of leaves and number of cupping were recorded at Day 3 after transplanting. Results showed significant differences in plant character for number of leaves. Brassica oleraceae var capitata cv KY Cross had better performance an high quality of growth performance compared to Brassica oleraceae var capitata cv Delta Green.